Civil Officials' Self-Control and Investment Planning Intentions: A Study in Financial Management: Pengendalian Diri Pejabat Sipil dan Niat Perencanaan Investasi: Sebuah Studi dalam Manajemen Keuangan - Hariyanto, Wiwit; Arizanda Rahayu, Ruci; Noor Abidin, Fityan Izza; Hidayatullah, Muhammad Tegar; Huda, Miftahul (Universitas Muhammadiyah Sidoarjo, 2023)
Abstract: This research examines the influence of self-control levels among civil officials in relation to their investment planning intentions, considering the importance of effective financial management for future income and expenses. Utilizing purposive sampling, data from 77 respondents were collected through a questionnaire. The study employs Smart PLS software and partial least squares (PLS) analysis to test hypotheses. The findings underscore the significance of technology readiness and unveil implications through a SINTA-ranked journal publication, national seminar article, and intellectual property rights. As financial aspirations persist among individuals, especially those with families, many remain hindered by financial constraints. This study underscores the urgent need to address these challenges, offering insights for informed financial decision-making and goal realization. Highlight: Examining Self-Control and Investment Intentions: This study explores how self-control levels among civil officials influence their intentions for investment planning, emphasizing the crucial role of effective financial management in shaping future income and expenses. Methodology and Analysis: Employing purposive sampling and Smart PLS software with partial least squares (PLS) analysis, data from 77 respondents are analyzed to test hypotheses related to technology readiness and its implications. Addressing Financial Challenges: With enduring financial aspirations, especially within families, many individuals face constraints. The study underscores the urgency of tackling these challenges, providing insights for informed financial decision-making and achieving financial goals. Keyword: Self-Control, Investment Planning, Financial Management, Technology Readiness, Financial Constraints